Illuminated the analysis of the translation is: systemic functional linguistics strikes Yoda back - Espindola, Elaine Baldissera (2013)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-Graduação em Inglês e Literatura Correspondente, Florianópolis, 2010